THU0083 Bone mineral density measurements are suitable for rapid quantification of skeletal destruction in rats with adjuvant arthritis. (1st June 2001) - Feige, U; Koch, A; Bolon, B
Abstract : Background: Reduced bone mineral density [BMD] is one of the major features of arthritis in both humans and animals. In a previous study, we showed that BMD was significantly decreased in both the femorotibial (knee) and tibiotarsal (ankle) joints of male Lewis rats with mycobacteria-induced adjuvant arthritis (AdA) even though clinical inflammation was most pronounced in the ankle. 1 Objectives: The present experiment measured BMD in the ankles and knees of male Lewis rats with AdA to (1) define which region provides the greatest sensitivity as a rapid screen for anti-arthritic efficacy and to (2) determine the progression of chronic bone loss at these sites. Methods: AdA was induced on day 0 (body weight of rats, 100 g) by subcutaneous injection of heat-killed mycobacteria in oil; the day of AdA onset (as defined by paw swelling) was day 9. BMD was assessed in knees and ankles on days 12, 13, 14, 15, 16, 17, 18, 25 or 35 (6 normal and 6 arthritic rats/day) using dual energy x-ray absorptiometry (DEXA; Model 4500A, Hologic, Waltham, MA). Results: In control rats, mean BMD for both sites increased by 20% between days 0 to 12, remained constant between days 12 to 18, and then increased again by 10% (ankle) or 25% (knee) by day 35. In AdA rats, hind paw volume relative to baseline values doubled between days 9 to 11 and then increased by another 1.5- to 2-fold to plateau on day 15. Mean knee BMD in AdA animals was 85% of control levels on day 12, fell to 75% by day 15, and ended at 55% on day 35. In contrast, mean BMD in ankles of AdA rats was comparable to control values through day 14, was 85% of controls on days 15 to 18, and decreased to 60% on days 25 and 35. Conclusion: Our data indicate that BMD loss occurs earlier and to a greater degree in the knee of rats with AdA, suggesting that this joint could be a useful site for rapid quantitative screening for skeletal destruction. Reference: Feige, et al . Ann Rheum Dis. 2000;59(Suppl I):148